Pengaruh Real Time Personalization dan AI Driven Recommendation System terhadap Purhase Decision pada Platform E-Commerce dengan Social Media Influence sebagai Variabel Mediasi: Studi pada Pengguna Shopee di Kota Semarang - Aulia Khalistasani Astungkara Gusrin; Rizal Hari Magnadi (Faculty of Economics and Business Diponegoro University, 2026)
This study aims to analyse the effect of real-time personalisation and AI-driven recommendation systems on purchase decisions among Shopee users in Semarang City, with social media influence as a mediation variable in the context of AI-based e-commerce. A quantitative approach was used to collect primary data through a Google Forms-based questionnaire from 96 respondents in Semarang City. Data analysis was performed using SmartPLS software using the SEM-PLS method. The findings indicate that AI-driven recommendation systems have a positive and significant effect on purchase decisions, whereas real-time personalisation does not. Furthermore, social media influence has not been shown to mediate the relationship between the independent variables and purchase decisions. This study offers novelty by integrating AI-based technological stimulus variables and social factors into a single research model and by examining the mediating role of social media influence in a local e-commerce context, specifically among Shopee users in Semarang City. E-commerce managers need to prioritise optimising AI recommendation algorithms to improve purchasing decisions, while using social media as a supporting factor.